Trust at Work: A Study on Faith and Trust of Protestant Entrepreneurs in China - Tong, Joy Kooi-Chin (Religions, 2016)
There is much talk about the trust crisis in China and the possible role of religion in rebuilding China's moral order. This study is an attempt to examine religion's impact on the emerging market economy in China, focusing on trust in business relations that might be generated by the Christian faith. Based on 43 in-depth interviews with Christian entrepreneurs in China, our study shows that the majority of our respondents tend to be: (1) more willing to be trustworthy after becoming Christians; (2) trusting people who share their faith more than others; (3) perceiving religious persons, regardless of what that religion is, as more trustworthy than the non-religious. Our study shows that religiosity is used by many Christian entrepreneurs as a category to guide their decision-making and that it is significant in stimulating and maintaining trust in and from others.